Beyond the Golden Compass : [videorecording (DVD)] : the magic of Phillip Pullman - Isbouts, Jean-Pierre; Brinkley, James (Koch Vision, 2007)
Concepts developed in Philip Pullman's book The Golden Compass are discussed and analyzed. Includes an exclusive interview with Philip Pullman, in-depth interviews with experts of history and literature, re-enactments shot in the story's actual locations, and more.